2021
DOI: 10.21037/atm-21-1783
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring glucocorticoids in patients with severe COVID-19: a narrative review

Abstract: To discuss the pathogenesis of severe coronavirus disease 2019 (COVID-19) infection and the pharmacological effects of glucocorticoids (GCs) toward this infection. To review randomized controlled trials (RCTs) using GCs to treat patients with severe COVID-19, and investigate whether GC timing, dosage, or duration affect clinical outcomes. Finally. to discuss the use of biological markers, respiratory parameters, and radiological evidence to select patients for improved GC therapeutic precision.Background: COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 112 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…1 g MP) when given prophylactically before the initiation of CPB. However, benefits of GC to regulate dysregulated inflammation have mostly been observed in critical care studies adopting a mild-to-moderate dose of GC, as we have seen in inflammation-mediated conditions, such as acute respiratory distress syndrome [ 21 23 ]. In our study, we will implement an initial dosage of 4 mg/kg/d MP on POD 1 and taper it to 1 mg/kg/d on POD 3.…”
Section: Discussionmentioning
confidence: 99%
“…1 g MP) when given prophylactically before the initiation of CPB. However, benefits of GC to regulate dysregulated inflammation have mostly been observed in critical care studies adopting a mild-to-moderate dose of GC, as we have seen in inflammation-mediated conditions, such as acute respiratory distress syndrome [ 21 23 ]. In our study, we will implement an initial dosage of 4 mg/kg/d MP on POD 1 and taper it to 1 mg/kg/d on POD 3.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically methylprednisolone achieves higher lung-to-plasma ratios in animal models than dexamethasone, and smaller trials have demonstrated its superiority to dexamethasone; however, the therapeutic dosing was not equivalent between groups [21,22]. Regarding the best possible initiation time for the treatment, the current evidence suggests their usage in the second week of infection, when inflammatory instead of infectious mechanisms predominate [8,23,24]. In trials so far, different dosage regimes have been reported in patients with severe COVID-19, from consistent doses throughout the treatment course, to the administration of a tapering dose, or the administration of pulse doses for a short period [8].…”
Section: Glucocorticoids In the Management Of Covid-19 Patientsmentioning
confidence: 95%
“…Glucocorticoids have been widely used in the previous severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS) epidemics and ARDS in general; however, the data regarding their efficacy were contradictory and generally of low quality [6]. They exert potent antiinflammatory effects across both innate and adaptive immune systems through the DNA-dependent regulation of antiinflammatory proteins, non-genomic modulation of inflammation, and direct protein interference of transcription factors such as nuclear factor kappa B [7][8][9]. In early 2020, a retrospective study of 201 patients admitted with confirmed COVID-19 pneumonia in Wuhan, China, provided the first evidence supporting their usage by demonstrating that treatment with methylprednisolone was associated with a reduced risk of death among patients with ARDS [10].…”
Section: Glucocorticoids In the Management Of Covid-19 Patientsmentioning
confidence: 99%
See 2 more Smart Citations